The Interface between Amazon Development and the Indigenous Communities: The Suruí emergence as subjects of political action - da Silva, Nathalia Thaís Cosmo; Ferreira Neto, José Ambrósio (Universidade Federal Rural do Rio de Janeiro, 2017)
This paper is a part of the results of a study aimed at analyzing the scenario of indigenous communities, verifying the interaction between the mechanisms of stability and change trigerred in the current development process. The main empirical basis of the Surui indigenous community is located between the Brazilian states of Rondônia and Mato Grosso. This group stands out in the current scenario for its ability to articulate with various groups in society, such as their engagement in new environmental projects, and in partnerships with several NGOs, including foreign, large organizations and universities. Having a past marked by the wood exploration and by the intrusion of settlers installed near their territory, Terra Indígena Sete de Setembro, due to the Integrated Program for Colonization, the current indigenous reality of the Suruí conjugates trajectories and temporalities that combine and clash from increased relationship with non-Indians. The methodology chosen was the case study, and the following data collection instruments were used: (a) Notes taking during the course "Economic Activities in Indigenous Lands" and on the reality in the villages of Suruí and (b) interviews with participants of the course, with the Surui, with political actors as well as academics involved in the issue of Rondônia development. The results indicate that there is a polarization between the political actors, the role of academia and the role of Indians in relation to the development process in Rondônia, so that the Suruí emerge as subjects of political action.